Audit Komunikasi Strategi Sosialisasi Program Hotline Pelayanan Publik LAPOR Hendi - Nimas Sintha Naurisma; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This research is based on the problem of the large number of people in the city of Semarang who submit their complaints to the government in unofficial media, while in fact the government already has an official complaint channel called LAPOR Hendi. This official complaint channel should be used and utilized by the public as a medium that channels all complaints and aspirations to the government. The purpose of this study was to conduct a communication audit on the socialization activities of the LAPOR Hendi program. This research will explain how the government carried out socialization activities to introduce the LAPOR Hendi program to the people of Semarang City. This research is a descriptive qualitative study that uses the organizational information theory of Karl Weick and the theory of SOR (Stimulus, Organisms, Reasons). Based on the results of the research, the socialization carried out by the Semarang City Government did not have a careful planning. The results showed that the socialization planning carried out by the government did not pay attention to Anne Gregory's 10 Planning. Analysis was not carried out by the government, the government did not conduct analysis and research before carrying out the socialization of the LAPOR Hendi program. The government has known the objectives of the socialization as the implementer of the socialization, however, the government does not use primary data and secondary data in determining the objectives of the socialization. The public who can participate in the socialization of the LAPOR Hendi program all the people of Semarang City. The messages conveyed in socialization are not planned and arranged in detail, there are no indicators of messages that will be conveyed in the socialization. The government does not understand the strategies they use in socialization. The strategy used in the socialization of the LAPOR Hendi program is Ritual. The government uses tactics in carrying out outreach, but the government does not develop existing tactics or come up with new tactical ideas. The government uses tactics in carrying out outreach, but the government does not develop existing tactics or come up with new tactical ideas. The government always conducts outreach to the public, there is no deadline for socializing the LAPOR Hendi program. The socialization that will be carried out has been planned in the annual work plan. The government uses the tools and equipment used for socialization. The operational costs have also been planned in the annual work plan. The government carries out monitoring and evaluation after the socialization is carried out. However, the government is not maximal in ensuring the message is received by the audience. The government conducts a review to find out whether the socialization that has been carried out is going well.